1972
DOI: 10.1037/h0032222
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of insufficient, sufficient, and oversufficient rewards: A clarification of equity theory.

Abstract: The present research investigated the distribution of rewards under conditions of different total amounts of money Results indicate that subjects divided money equally between themselves and a co-worker with equal inputs, only when the total amount of reward available was congruent with an internal standard of fair pay, when the total amount was either substantially more or substantially less than this amount, the subjects gave proportionately more to themselves These results are used as the basis for an argum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

1979
1979
2003
2003

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 15 publications
1
31
0
1
Order By: Relevance
“…Other than the impact of resource scarcity on distributive judgments (e.g., Lane & Messé, 1972;Skitka & Tetlock, 1992), the role of more impersonal, structural features of the distributive environment has received little attention (for a recent exception examining the role of organizational structure on perceptions of fairness, see Schminke, Cropanzano, & Rupp, 2002). Political, philosophical, and economic theorists, however, tell us that our judgments of social justice should take into account a wide range of structural or situational features, which-if left unstudied-may confound results or greatly limit one's ability to draw inferences from the experimental setting.…”
Section: Experiments 1: Meritocracy and Frame Of Referencementioning
confidence: 99%
“…Other than the impact of resource scarcity on distributive judgments (e.g., Lane & Messé, 1972;Skitka & Tetlock, 1992), the role of more impersonal, structural features of the distributive environment has received little attention (for a recent exception examining the role of organizational structure on perceptions of fairness, see Schminke, Cropanzano, & Rupp, 2002). Political, philosophical, and economic theorists, however, tell us that our judgments of social justice should take into account a wide range of structural or situational features, which-if left unstudied-may confound results or greatly limit one's ability to draw inferences from the experimental setting.…”
Section: Experiments 1: Meritocracy and Frame Of Referencementioning
confidence: 99%
“…When these results are combined with those of Lane and Messe (1972), they indicate the important effect of the amount of money available on allocation decisions. Lane and Messe found that the total amount of monetary reward influences how individuals allocate it between themselves and others.…”
Section: Downloaded By [York University Libraries] At 05:32 05 Januarmentioning
confidence: 64%
“…Other empirical studies have found that a restrained self-interest on the part of the allocator becomes manifested when the allocation rule is kept in complete secrecy (Guzzo, et al, 1984). Under these circumstances, the equity prin ciple has its strongest negative impact when the means of allocation are fully dis closed (Lane & Messé, 1971). In addition to preventing the revelation of self-inter est, the intention to eliminate the availability of information for group members to compare themselves with others (and thus the possibility of experiencing inequity) is another reason that has been identified to cause allocators to conceal information regarding the implementation of the reward system (Guzzo, et al, 1984;Leventhal, 1976).…”
Section: Intraorganizational Issuesmentioning
confidence: 99%
“…As Hegtvedt (1987) notes, the influence of reward scarcity on allocation preferences defines a major structural constraint in the distribution process. Studies have shown that when rewards are extremely scarce-threatening basic survival-or when they are unlimited and determined by total member contributions, the equity principle is generally preferred (Cook & Yamagishi, 1983;Galston, 1980;Hegtvedt, 1987;Lane & Messé, 1971;Lawler, 1981). When rewards are fixed and relatively scarce, however, concern for the group as a whole is enhanced and the equality principle is considered more appro priate (Cook & Yamagishi, 1983;Hegtvedt, 1987;Lane & Messé, 1971).…”
Section: Intraorganizational Issuesmentioning
confidence: 99%
See 1 more Smart Citation